Intervention of Climate Smart Agriculture Practices in Farmers Field to Increase Production and Productivity of Winter Maize in Terai Region of Nepal - Gairhe, J. J.; Adhikari, M. (Journal of the Institute of Agriculture and Animal Science, 2018)
Climate change has been the burning issue in agriculture sector. The research world is focused on developing appropriate technology, innovations and concept to cope up this change. The Climate Smart Agriculture [CSA] has been adapted globally for cultivation and crop management in changing context without compromising yield and productivity. The CSA involves wide range altered techniques and innovations like using resilient varieties, water management, zero tillage, legumes incorporation, cover cropping, site specific fertilizer management, variation in planting date etc. Grounding on the similar practices and principles of CSA, the research in maize was conducted in 2014 in farmers' field of Eastern Nepal. Three progressive farmers with 1 hector of land were selected and Maize was cultivated using Zero tillage seed cum fertilizer driller tractor. This field experiment considers farmers as replication with six different treatments. All treatments differ to each other based on nutrient management, water management, residue management, tillage practice, crop establishment, and inclusion of legumes in the cropping system. Six treatments are coded as follows: Current Irrigated (CI), Improved Irrigated Low (IIL), Improved Irrigated High (IIH), Climate Smart Agriculture-Low (CSA-L), Climate Smart Agriculture-Medium (CSA-M), and Climate Smart Agriculture-High (CSA-H). Significant impact of intervention was observed in yield and yield attributes in the trial with climate smart agriculture practices than in conventional practices of farmers. Plant density, ear number, filled grains per cob and grain yield was substantially higher in climate smart practices revealing CSA to be the appropriate technology to minimize potential loss of climate change.